A New Japan Volcanological Database - Fujita, Eisuke; Ueda, Hideki; Nakada, Setsuya (Frontiers in Earth Science, 2020)
For the purpose of the development of volcanology and its practical application to volcanic hazard mitigation, we are conducting a new project named the Integrated Program for Next Generation Volcano Research and Human Resources Development (INeVRH). This project began in 2026 and will end in 2025 and consists of four themes focusing on observation, forecasting, countermeasures, and a data-sharing system. This data-sharing system is named the Japan Volcanological Data Network (JVDN), which will serve as a platform that combines observation, forecast, and countermeasure data to provide information for the judgment at branch nodes of event trees for volcanic crises in the coming decades in Japan.